Answer:
sqrt 11
Step-by-step explanation:
Pythagorean theorem again. a^2+b^2=c^2. The hypotenuse is the c value. One of the legs is either a or b, doesn't matter which. So you can make the equation 5^2+b^2=6^2. 25+b^2=36. Subtract 25 from each side to isolate the b variable. You're left with b^2=11. Now you take the square root of each side to get b. This makes b= sqrt 11.
Read more on Brainly.com - https://brainly.com/question/12905664#readmore
Answer:
b=4
Step-by-step explanation:
a^2 + b^2 = c^2
substitute:
3^2+b^2=5^2
9+b^2=25
25-9=b^2
16=b^2
the square root of 16=4
b=4
check:
4 times 4 = 16
9+16+25